Características da carcaça e qualidade da carne de cordeiros terminados com diferentes proporções de resíduo úmido de cervejaria - Manzoni, Verônica Gindri (2019)
The experiment was conducted with the objective of evaluating the effect of increasing levels of wet brewery grains (WBG) as exclusive volume source on carcass characteristics, non-carcass components, tissue composition, centesimal, lipidic, instrumental and sensorial characteristics of meat of lambs finished in confinement. Thirty-two male lambs, uncastrated, weaned at 50 days of age and from crossbreeding between the Texel and Ile de France breeds were used. The diet was composed volume source, this being the WBG, and by concentrate, composed of disintegrated corn, soybean meal, calcitic limestone and mineral salt. The treatments were constituted by four levels of WBG as dietary bulk (% of DM), being: 31, 44, 57 and 70%. The lambs were slaughtered when they reached 34 kg of live weight. The treatments exerted a negative influence in a linear descending manner (P≤0.05) on the weights and yields of hot and cold carcass, carcass compactness index, conformation, fattening state and loin eye area. Among the regional cuts as they increased the level of WBG decreased (P≤0.05) the absolute weights of palette, trim and leg. Among the non-carcass components, only the total gastrointestinal content increased linearly (P≤0.05) with the elevation of WBG content. The best carcass characteristics were obtained with the inclusion of 31% WBG as a bulky food in the finishing of confined lambs. The tissue composition was not influenced (P>0.05) by the different levels of WBG used. The centesimal composition of the meat had similarities to the standards available in the literature presenting values of 76,37%; 1.06%; 5.06% and 19.08% for moisture, ashes, total lipids and protein, respectively, with a linear increase (P≤0.05) in the ashes and in the total lipids content. There was a linear increase in the proportion of saturated fatty acids (SFA) and a linear decrease in monounsaturated fatty acids (MFA) and, consequently, in the ratio of monounsaturated fatty acids and saturated fatty acids (MFA: SFA) as WBG in diets. The polyunsaturated fatty acids that are proven to be beneficial to human health, as well as the PFA: SFA and n6: n3 ratios presented values within the recommended range and showed no influence on the meat of lamb fed with different levels of wet brewery residue, thus demonstrating the potential of WBG use. The treatments did not influence the instrumental characteristics: pH 0, 3, 6 and 24 hours after slaughter (6.63, 6.25, 5.98 and 5.56 respectively), color(L*= 38,63; a*=17,17 e b*= 6,22), Water retention capacity (76.05%), shear force (2.72 kgf / cm²), defrosting losses (12.47%) and cooking losses (24.22%) of the meat. Sensory analysis also showed no effect of different levels of RUC for the evaluated attributes. It is concluded that the WBG when used in levels between 31% and 70% as exclusive source of bulky in the diet of lambs finished in confinement does not promote changes in the instrumental and sensorial characteristics of the meat of the animals.